Food Waste and The UK's Grocery Retail Sector - McNulty-Skead, Tabitha (2018)
Every year approximately a third of all food produced around the world is wasted, costing the equivalent of one trillion US dollars and accelerating climate change and environmental degradation (FAO, 2011). At the same time, one in nine people are malnourished and the population continues to rise, resulting in a severe and unprecedented threat to global food security (FAO, 2015). Food waste is therefore a global sustainability crisis of alarming scale that requires urgent action. As a result, of the United Nation’s seventeen Sustainable Development Goals (SDGs,) SDG12.3 calls for global food waste to be halved by 2030 (UN, 2015). In the UK, food waste patterns closely match those observed across the developed world, with eighty-five percent of the country’s avoidable food waste produced by households and food manufacture (WRAP, 2017). The grocery retail sector sits at the centre of the food industry, connecting suppliers to consumers and holds large amounts of power and influence over both ends of the supply chain (Devin and Richards, 2018; Wilshaw, 2018). Supermarkets therefore have a critical role to play in contributing to the achievement of SDG 12.3.